Six-step operation strategy for direct self-control method of interior permanent magnet synchronous motors based on torque angle - Han, Byeol; Lee, June Seok; Bak, Yeongsu; Lee, Kyo Beum (Journal of Power Electronics, 2021)
This paper proposes a six-step operation strategy for direct self-control (DSC) method of interior permanent magnet synchronous motor (IPMSM) based on the torque angle. Conventional DSC methods for induction motors (IMs) have been studied for railway applications since these methods are suitable for controlling high-power traction drives and for extending voltage utilization through a six-step inverter operation. However, IPMSMs controlled via conventional DSC methods for IMs cannot be properly controlled through a six-step operation since the torque angle is not considered. In addition, synchronous frame rotation causes a phase error at high speeds owing to the time delay of digital controllers. This paper presents a torque angle compensation that improves the dynamic performance. The effectiveness of the proposed DSC method was verified through experimental results.
Keywords: Digital controllers; Direct self control; Dynamic performance; Interior permanent magnet synchronous motor; Inverter operations; Operation strategy; Railway applications; Synchronous frame; Direct self-control; Flux-weakening (FW) control; Interior permanent magnet synchronous motor; Maximum voltage utilization; Six-step operation